Comparative study about knowledge, attitude and practice study of fixed dose combination among junior residents and interns of a tertiary care hospital - Korde, Rupa Arun; S., Radhika M.; Gandigawad, Priya; Sori, Ravi; ., Amruth (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Fixed Dose Combinations (FDCs) are defined by the World Health Organization (WHO) as combination of two or more active ingredients in a fixed ratio of doses. According to the FDA, “two or more drugs may be combined in a single dose when each component makes a contribution to the claimed effects, and the dosage of each component (i.e., amount, frequency, and duration) is such that the combination is safe and effective for significant patient population requiring such concurrent therapy. However, certain disadvantages like incompatible pharmacokinetics, inflexible dose ratio, increased toxicity and cost, contraindication of one component of the FDC decreased their utility. Adverse effect of any one component also limits their use. The aim of the study is to compare and evaluate the knowledge, attitude and practices about prescribing fixed dose combinations among junior resident doctors (JRs) and interns (INTs) at SDM College of Medical Sciences and Hospital Dharwad. Methods: A cross-sectional study was carried out in 134 doctors using pre-validated 10 item questionnaire with details of participant’s information followed by questions regarding knowledge, attitude and prescribing practice of fixed dose combinations was used as a tool, administrated to all the resident doctors and the collected data was analysed. Results: Our study revealed that knowledge about FDCs was lacking in JRs and INTs. They were not able to point out the actual advantages and disadvantages of FDCs. Knowledge about rational/irrational, banned FDCs and availability of WHO EML was also lacking. Conclusions: There is need to improve knowledge about rationality, essential medicine list, usage and banned FDCs in undergraduate medical students to promote the rational use of drugs.